THE EFFECT OF MIND MAPPING ON THE FUNCTION OF GROUPS COMMUNICATION IN PUBLIC SPEAKING AND COMMUNICATION THEORY SUBJECT - Heny Triyaningsih (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2022)
The purpose of communication is to change attitudes, opinions, behavior, and social society. In particular, the interaction between lecturers and students normalizes the message to arrive completely and optimally, including in the courses of communication theory and public speaking. Based on these needs, the use of mind mapping is the object of research as a way of optimizing group communication by formulating problems related to the mechanism for making mind maps and their effect on learning in group communication. The method used in this study is descriptive qualitative analysis, namely by observing, collecting and presenting the data to be analyzed. The researcher concluded that the mechanism for making a mind map is to make a concept map on the material presented in class, the lecturer's explanation and discussion. The influence of making mind mapping in the courses of communication theory and public speaking produces a very significant effect, namely based on the percentage of positive responses to the mind mapping and manufacturing stages and the effects on students, more than 75% respond positively compared to the negative effects.